Manipulação genética humana e suas implicações no sistema jurídico: a regulamentação jurídica das pesquisas genômicas em humanos frente aos princípios da Bioética - Souza, Mariana Vieira de (Universidade do Vale do Rio dos Sinos, 2021)
The present work has as its theme the implications on the legal system in response to the new techniques of human genetic manipulation provided by biotechnology. Scientific, jurisprudential and doctrinal research, followed by analysis and interpretation are used as a method to achieve this study. The analysis is necessary due to the various possibilities of use and commercialization that result from these innovations and is carried out based on the appreciation of proactive, proactivist and moderate doctrinal currents, noting antagonisms and consensus among them, as well as national and international jurisprudential and legislative trends regarding matters of similar nature. It is necessary, initially, to dismantle some of the most essential concepts to the subject, to then understand what genetic engineering is all about and how bioethics operates and can be applied to it. The aim of this study is to bring a future perspective in relation to genetic intervention in human beings, as well as its benefits and harms, and its correlation to human rights. Finally, in view of the unpredictability of the topic, it is clear that it is impossible to regulate a practice that has not yet been consolidated, however, it is plausible to require the observation of basic constitutional and bioethical principles when faced with the practical issues that arise with the manipulation of the human gene
Keywords: Bioética; Bioengenharia genética; Biodireito; Dignidade humana; Bioethics; Genetic Bioengineering; Biolaw; Dignity of the human person